Criminal Liability for Journalists for Reporting the Identity of Children Facing the Law - Susanto, Joko; Martitah, Martitah; Sulistianingsih, Dewi; Mursyid, Ali Masyhar; Utari, Indah Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The shift from print, television, and radio to online media has made it simpler to obtain a variety of current news sources. Regretfully, despite the ease of access, not all news meets journalistic ethics and legal requirements, including those regarding minors in legal trouble (ABH). This article finds that there are still media offices that do not meet the standards of press regulation, which is governed by Press Council Regulation Number 1/Regulation-DP/II/2019, concerning the Guidelines for Child-Friendly News (PPRA) and Article 5 in the journalistic code of ethics, namely by producing news that is not child-friendly. This research uses 2 (two) theories, namely: Social Responsibility Press Theory and the theory of the relationship between criminal liability and criminal acts, with the research method used being normative juridical with a type of prescriptive research that is a literature study. The type of data used is secondary data. By analyzing the news of several online media that are still disclosing photos or publishing on ABH's identity, ABH's identity should be kept secret, aiming for ABH to be accepted in the community, if ABH's identity is revealed, it is feared that in continuing his life the child will be difficult to accept in society, especially if he is labeled as a